Detection of Epstein-Barr virus and Kaposi's sarcoma-associated herpesvirus DNA in CSF from persons infected with HIV who had neurological disease. Issue 2 (1st August 1998) - Brink, N S; Sharvell, Y; Howard, M R; Fox, J D; Harrison, M J G; Miller, R F
Abstract : OBJECTIVES: To determine the frequency and clinical relevance of Epstein-Barr virus (EBV) and Kaposi's sarcoma associated herpesvirus (KSHV) DNA detection in the CSF from patients infected with HIV. METHODS: Cerebrospinal fluid was obtained prospectively from 115 consecutive patients infected with HIV undergoing diagnostic lumbar puncture for investigation of neurological disease. Amplification of DNA was performed using a nested polymerase chain reaction (PCR) for detection of EBV internal repeat and KSHV minor capsid sequences. RESULTS: EBV DNA was detected in the CSF supernatant of 18 patients. This included all patients with primary CNS lymphoma (seven patients) or a combination of systemic and CNS lymphoma (two patients). By contrast EBV DNA was not detected in the CSF supernatant of any patient with systemic, but not CNS, lymphoma (10 patients). EBV DNA was also detected in the supernatant of nine further patients without a diagnosis of lymphoma at the time of lumbar puncture, two of whom subsequently developed CNS lymphoma. No EBV DNA was detected in CSF supernatant from the remaining 87 samples (two of these patients subsequently developed lymphoma). KSHV DNA was detected in the CSF of two patients, one had systemic (but not CNS) lymphoma and the other did not have lymphoma. CONCLUSION: A diagnosis of CNS lymphoma is strongly associated with the presence of EBV DNA in CSF. In the absence of clinical and radiological features of CNS lymphoma, the presence of detectable CSF EBV DNA may predict subsequent tumour development. KSHV DNA is rarely detected in CSF in this patient group and shows no correlation with lymphoma or other neurological disease.